1993
DOI: 10.1007/bf01518520
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of human tumor cell lines to anti-p185HER2 monoclonal antibodies

Abstract: The HER2 protooncogene encodes a receptor tyrosine kinase, p185HER2. The overexpression of p185HER2 has been associated with a worsened prognosis in certain human cancers. In the present work we have screened a variety of different tumor cell lines for p185HER2 expression using both enzyme-linked immunosorbent and fluorescence-activated cell sorting assays employing murine monoclonal antibodies directed against the extracellular domain of the receptor. Increased levels of p185HER2 were found in breast (5/9), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
252
6
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 439 publications
(275 citation statements)
references
References 51 publications
16
252
6
1
Order By: Relevance
“…HER2 oncogene in human cancer therapeutics MM Moasser were engineered for optimum participation in antibodydependent cellular cytotoxicity (ADCC) or complementdependent cytotoxicity (CDC), and indeed trastuzumab is much more efficient than its murine counterpart in mediating ADCC (Carter et al, 1992;Lewis et al, 1993;Tokuda et al, 1996). Trastuzumab has reduced cell culture antiproliferative activity compared with the murine 4D5, but equally potent antitumor efficacy in mouse xenograft models (Tokuda et al, 1996;Baselga et al, 1998;Clynes et al, 2000).…”
Section: D5 Inhibits Growth In Vivomentioning
confidence: 99%
“…HER2 oncogene in human cancer therapeutics MM Moasser were engineered for optimum participation in antibodydependent cellular cytotoxicity (ADCC) or complementdependent cytotoxicity (CDC), and indeed trastuzumab is much more efficient than its murine counterpart in mediating ADCC (Carter et al, 1992;Lewis et al, 1993;Tokuda et al, 1996). Trastuzumab has reduced cell culture antiproliferative activity compared with the murine 4D5, but equally potent antitumor efficacy in mouse xenograft models (Tokuda et al, 1996;Baselga et al, 1998;Clynes et al, 2000).…”
Section: D5 Inhibits Growth In Vivomentioning
confidence: 99%
“…It derivates from a murine antibody (called 4D5 (Fendly et al, 1990;Lewis et al, 1993) and it was humanised for clinical administration. The hypervariable domain remains similar to the animal domain, but the other 95% is similar to human IgG1.…”
Section: Monoclonal Antibodymentioning
confidence: 99%
“…However, the entire BRCA1 protein sequence is claimed to be present in both forms based on comparisons with recombinant protein produced in vitro or in vivo. We have shown that the analysis of BRCA1 subcellular localization has been complicated by the fact that a crucial antibody (C-20, Santa Cruz) crossreacts with the epidermal growth factor receptor (EGFR) and Her2 (Wilson et al, 1996) which are frequently overexpressed in human breast and ovarian cancers and malignant cell lines (Lewis et al, 1993;Earp et al, 1995). The level of EGFR expression in the MDA-MB-468 cells used to characterize BRCA1 secretion is particularly high (Wilson et al, 1996;Filmus et al, 1985).…”
Section: Introductionmentioning
confidence: 99%